Efektifitas Gambar dan Diorama untuk Mempelajari Wujud Alam - Zuhri Nurendah Puspitadewi; Anwar Senen (Jurnal Didaktika Pendidikan Dasar, 2023)
This study aims to find out the effect diorama media on social studies learning outcomes of 5th grade students at State Elementary School 2 Janturan, Pengasih, Kulon Progo. This study was a quasi experimental design with non-equivalent control group design’s type. Subject in this study was 59 fifth-grade students elementary school. The experimental group was treated with diorama media, while the control group was treated with picture media. Data collection technique were observation, test, and documentation. Descriptive statistic were used to analyse the data in this study with mean test of posttest between the experimental and control group with N-Gain test. Based on the data analyse showed than the mean test of experimental group was 85.36 which was categorized on very good level and the mean test of control group was 78.25 which was categorized on good level. The result of this study supported by the result of N-Gain test from experimental group was bigger than control group the was .7 > .3.